PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI SISWA YANG TERLAMBAT DI SMAN 1 MASBAGIK - Nurfitri, Umami; Ariska, Desi; Anwar, Nurul (JKP (Jurnal Konseling Pendidikan), 2024)
There are still some students who violate school rules, for example, students often come late to school. Based on this, the purpose of this study was to find out the role given by the Guidance and Counseling teacher in overcoming the problem of students coming to school late at SMAN 1 Masbagik. The results of this study concluded that the role given by the Guidance and Counseling teacher was one of them by providing guidance and direction as well as implementing individual counseling to students who came late to school. The reasons for students arriving late varied, there were students who said they were late getting up in the morning and there were also students who said they were tired of helping their parents after school so that the next morning they woke up late the next morning, and there were also students who reasoned that they were lazy to take math lessons. With the provision of individual counseling services by Guidance and Counseling teachers, it can be seen that there is a decrease in students coming to school late. Therefore, the implementation of individual counseling services can overcome the problem of students coming late to school at SMAN 1 Masbagik